Past and future in the time talk of teenage learners of English : a longitudinal study of the acquisition of L2 English by three students in the language support programme of an Irish post-primary school - McGarry, Deirdre M. (Trinity College (Dublin, Ireland). School of Education, 2015)
This study investigates aspects of the English language development of three teenage learners, (native speakers of Polish, Malayalam and Lithuanian) who were enrolled in the language support programme of an Irish post-primary school. The study follows the learners’ progress over four school years and adopts a descriptive non-experimental quantitative approach. The analysis is based on samples of written production which were obtained using a process designed to encourage relatively spontaneous writing, with the focus on meaning rather than form. These language samples were transcribed into CHAT format, and then comprehensively coded, providing a learner corpus of over 72,000 words. The data was analysed with the aid of the CLAN suite of programs.
Keywords: Education, Ph.D.; Ph.D. Trinity College Dublin